Factores de Riesgo Psicosociales que se Relacionan con el Estrés Laboral en los Trabajadores de una empresa minera (2022)
The present investigative work arose with the purpose of determining the relationship between psychosocial risk factors and work stress of workers in the water plant and maintenance area of the multinational Cerrejón Limited, for which it was approached under a type of quantitative, descriptive research. With a non-experimental design,